Mengoptimalkan Potensi: Pendekatan Teoritis Dan Praktis Dalam Manajemen Sumber Daya Manusia Dan Karyawan - Chaerul Rizky; Ibnu Hajar; Muhammad Fahri; Raihan Faturrahman Syahri (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
This research aims to investigate theoretical and practical approaches in optimizing the potential of human resources and employees. The research method used is a literature review with a qualitative approach to explore the conceptual framework supporting effective HR management practices. The literature review includes an in-depth review of relevant academic literature, covering key concepts in HR management such as motivation, leadership, career development, and performance measurement. Critical analysis of various theories and models helps in understanding the complexity and dynamics of HR management. The findings of this literature review indicate that theoretical approaches provide a solid conceptual foundation for understanding the basic principles in HR management, while practical approaches enable the implementation of strategies appropriate to the organizational context. The integration of theory and practice is key to developing effective and sustainable HR management strategies. The findings of this literature review provide valuable insights for practitioners in designing and implementing successful HR management practices. By understanding the theoretical framework and applying it contextually, organizations can optimize the potential of their human resources and employees, thereby enhancing organizational performance and competitiveness in the dynamic global market.